Single Polymer Chain Surface Area as a Descriptor for Rapid Screening of Microporous Polymers for Gas Adsorption - Laura Leay; Flor R. Siperstein (Adsorption Science & Technology)
The presented work shows that a qualitative assessment of the trends in surface area in a given microporous polymer family can be obtained by analyzing the properties of a single polymer chain. We analyzed the properties of polymers of intrinsic microporosity (PIMs) that contain imide groups (known as PIM-PIs) and obtained the surface area of available PIM-PIs and proposed some hypothetical structures that can result in higher surface areas and potentially more favourable properties for adsorption. The advantage of the proposed method is that it allows for a rapid screening of potential monomers avoiding the need to perform computationally expensive calculations.